Analisis Kondisi Keuangan Pemerintah Kota Sibolga Tahun 2018-2022 - Deliana, Deliana; Frans Marhuasa Simamora, Arne; Hidayah Napitupulu, Ilham (Journal of Accounting and Finance Management, 2024)
This research was aimed to know financial condition of government Sibolga for the years 2018-2022 from efficiency of PAD ratio, effectiveness of PAD ratio, expenditure compatibility ratio and Financial Dependency Ratio. The research used is analitical descriptive. The data collection techniques used in this research were field research and library research. Descriptive and ratio analysis was used to appraise efficiency of PAD ratio, effectiveness of PAD ratio, , expenditure compatibility ratio and Financial Dependency Ratio. The result of this research pointed that (1) efficiency of PAD ratio of Sibolga for each year was 1,59% in average which mean efficiency of PAD was already efficient. (2) The Government of Sibolga is still less effective in managing PAD with an average effectiveness ratio of 76.20%. (3) the highest ratio results from operating expenditures is 85,89% in 2021 and the lowest ratio in 2018 is 77,58%. The highest ratio of capital expenditures to the total expenditure is 22,39% in 2018 and the lowest ratio in 2019 is 14,04%. The Government of Sibolga still prioritizes operational expenditure compared to capital expenditure.(4) Financial Dependency Ratio of Sibolga government during 2018-2022 is 83.88% categorized very high, this condition shows the dependency level of Sibolga Goeverment is very high to the central government.